Functional resistance training program reduces injury risk in Australian Football players - Frazer, C.; Mendis, D.; Blanch, P.; Hides, J. (Journal of Science and Medicine in Sport, 2024)
Introduction: In the Australian Football League (AFL), players with a cross-sectional area (CSA) of the lumbar multifidus muscle below 8.2cm2, significantly increase the prospective likelihood of a time loss lower limb injury. A subsequent intervention study, implementing a functional resistance training program involving players with a multifidus CSA below 8.2cm2, increased this CSA value. The aim of this current study, as a final review of the Translating Research into Injury Prevention Practice (TRIPP) protocol, is to ascertain whether this increase in multifidus muscle size then leads to a reduction of time loss lower limb injury risk.